Performance of an ELISA and Indirect Immunofluorescence Assay in Serological Diagnosis of Zoonotic Cutaneous Leishmaniasis in Iran - Sarkari, Bahador; Ashrafmansouri, Marzieh; Hatam, GholamReza; Habibi, Parvaneh; Abdolahi Khabisi, Samaneh (Interdisciplinary Perspectives on Infectious Diseases, 2014)
Serological assays have been extensively evaluated for diagnosis of visceral leishmaniasis (VL) and considered as a routine method for diagnosis of VL while these methods are not properly evaluated for diagnosis of cutaneous leishmaniasis (CL). This study aimed to assess the performance of indirect immunofluorescent-antibody test (IFA) and enzyme-linked immunosorbent assay (ELISA) for serodiagnosis of cutaneous leishmaniasis in Iran. Sixty-one sera samples from parasitologically confirmed CL patients and 50 sera from healthy controls along with 50 sera from non-CL patients were collected. Antigen was prepared from promastigotes and amastigotes of Leishmania major. IFA was used to detect anti-Leishmania IgG while ELISA was used to detect anti-Leishmania IgM, total IgG, or IgG subclasses (IgG1 and 4). ELISA, for detection of total IgG and IgM, showed sensitivity of 83.6% and 84.7% and specificity of 62.7% and 54.6%, respectively. Sensitivity and specificity of ELISA for detecting IgG1 and IgG4 were 64%, 75% and 85%, 49%, respectively. Sensitivity and specificity of IFA were 91.6% and 81%. Conclusion. Findings of this study demonstrated that serological test, especially IFA, can be used for proper diagnosis of CL.